Quantitative analysis of behavior: intersections between Psychology and Economic Sciences on the study of decision-making. (Brazilian Journal of Behavioral and Cognitive Therapy, 2022)
New developments in the emerging field of Behavioral Economics have been madetowards an updated account of what would be classically viewed as “irrational behavior”,yielding significant changes in classical economic models for studying decision-making.However, Michie et al. (2011) points out that an evidence-based behavior model withinternal consistency has not been yet developed. In most applications, theories are rooted incommon sense or intuitive knowledge assumptions on behavior. We argue that BehavioralPsychology offers a relevant body of evidence and theories that can help EconomicSciences and Behavioral Economics advance towards a robust, evidence-basedcomprehension of the nature of a behavior of interest. Such contributions can be used tobetter plan applications, as it also grants a better understanding of independent variablesthat are key to predict behavioral outcomes. Relevant paths through which BehavioralPsychology and Behavioral Economics can benefit from better establishing communicationbetween areas will be discussed.
Keywords: behavior analysis; molar analysis; behavioral analysis; decision-making; feedback function.